A Systematic Review of Home-Setting Psychoeducation Interventions for Behavioral Changes in Dementia: Some Lessons for the COVID-19 Pandemic and Post-Pandemic Assistance - Alves, Gilberto Sousa; Casali, Maria Eduarda; Veras, André Barciela; Carrilho, Carolina Gomes; Bruno Costa, Eriko; Rodrigues, Valeska Marinho; Dourado, Marcia Cristina Nascimento (Frontiers in Psychiatry, 2020)
Background: Impacts of social isolation measures imposed by COVID-19 Pandemic on mental health and quality of life of older adults living with dementia and their caregivers remain unexplored. Studies have shown that psychoeducational and psychosocial interventions can manage behavioral and psychological symptoms in dementia (BPSD) and reduce the emotional burden on family members when applied in home-setting scenarios. Method: a comprehensive systematic review of useful interventions for easing the BPSD burden in patients with dementia (PwD) and their caregivers in the context of COVID-19 quarantine was performed from January 2010-March 2020. Results: From a total of 187 articles retrieved from electronic databases (MEDLINE, LILACS, Cochrane and SCOPUS), 43 studies were eligible for this review. Most of the psychosocial and psychoeducational interventions described were person-centered strategies based on the cognitive-behavioral approach or informational tools to enhance care providers' knowledge of dementia. Most studies achieved successful results in handling BPSD and mood-anxiety symptoms of care providers, contributing to an overall improvement in dyad life quality. Conclusion: Evidence from the last few years suggest that low-cost techniques, tailored to the dyad well-being, with increasing use of technology through friendly online platforms and application robots, can be an alternative to conventional assistance during COVID-19 Pandemic. Nevertheless, the world’s current experience regarding the duration of the COVID-19 Pandemic and its effects on the cognition, behavior and life quality of PwD will demand research on preventive and protective factors of dementia and the pursue of efficient interventions in different scenarios.